Integrating Islamic Values into a Science Comic Book as an Instructional Media - Tamam, Badrud; Sutarja, Maria Chandra; Rakhmawan, Aditya; Mus'if, Ach. (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
This study examined the validity of a science comic book integrated with Islamic values. The development of the book followed the steps of ADDIE (Analyze, Design, Develop, Implement, and Evaluate). The product was validated by an expert in Islamic studies, an expert in instructional media, an expert in instructional material, and a science teacher. A questionnaire was used to obtain data validation results. The expert validation results showed a score of 3.8 for the integrated Islamic values, 3.5 for the material, 3.5 for the book function as instructional media, and 3.7 for the product practicality, with all scores falling into the